2019
DOI: 10.1080/00016489.2019.1616819
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic hydrops induced by different mechanisms responds differentially to spironolactone: a rationale for understanding the diversity of treatment responses in hydropic inner ear disease

Abstract: Endolymphatic hydrops induced by different mechanisms responds differentially to spironolactone: a rationale for understanding the diversity of treatment responses in hydropic inner ear disease ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The dose of desmopressin reported to induce EH models was variable, but there was evidence supporting increasing dosage and injection days can provide a more severe EH status in animal models at a low dose level ( Takeda et al, 2000 ; Katagiri et al, 2014 ). The dose of 4–6 μg/kg weight has been widely used for EH guinea pigs modeling ( Degerman et al, 2019 ; Jiang et al, 2019 ). Considering the potential for long-time medication tolerance, we increased the dose of desmopressin for our animal models ( Takeda et al, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…The dose of desmopressin reported to induce EH models was variable, but there was evidence supporting increasing dosage and injection days can provide a more severe EH status in animal models at a low dose level ( Takeda et al, 2000 ; Katagiri et al, 2014 ). The dose of 4–6 μg/kg weight has been widely used for EH guinea pigs modeling ( Degerman et al, 2019 ; Jiang et al, 2019 ). Considering the potential for long-time medication tolerance, we increased the dose of desmopressin for our animal models ( Takeda et al, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…In an experimental study, Degerman et al showed that spironolactone blocks the phosphodiesterase 4 (PDE4) pathway, involved in the generation of endolymphatic hydrops [ 222 ].…”
Section: Methodsmentioning
confidence: 99%
“…Imaging technology, including MRI, might be developed as a critical tool for evaluating ELH in animal models for MD. In a recent study, ELH in mice was assessed using a high resolution 9.4 T field strength MRI [41]. Furthermore, light sheet fluorescence microscopy (LSFM) can be used as a means to obtain highly resolved 3D visualization of endolymphatic fluid movements; this has enabled researchers to examine the entire inner ear of experimental animals, en bloc, with subcellular resolution.…”
Section: Confirmation Methods In Animal Models Of Endolymphatic Hydropsmentioning
confidence: 99%
“…We introduced fluorescein isothiocyanate dextran (FITC-dex) and artificial endolymph into the scala media of anesthetized guinea pigs via a glass micropipette (Fig. 2) [41]. When more than 2.5 mL of FITC-dex was injected into the scala media, FITC-dex was observed in the SSCs, utricle, and endolymphatic duct.…”
Section: Confirmation Methods In Animal Models Of Endolymphatic Hydropsmentioning
confidence: 99%